Psychometric Properties of the Persian Food-Life Questionnaire Short Form among Obese Breast Cancer Survivors - Babak Nejati; Chung-Ying Lin; Mark D Griffiths; Amir H Pakpour (Elsevier, 2020)
Objective: To assist weight control among women with breast cancer, improving their food attitudes may be an effective method. Therefore, the present study validated a short instrument assessing food attitudes (i.e., the Short Form of the Food-Life Questionnaire [FLQ-SF]) among Iranian women with breast cancer who are overweight. Methods: Women with breast cancer who were overweight (n = 493; mean ± standard deviation age = 52.3 ± 10.7 years) participated in the study. All of them completed the FLQ-SF, questions designed using the theory of planned behavior (TPB; including subjective norm, perceived behavioral control, and behavioral intention), and food frequency questionnaire (FFQ). Both classical test theory and Rasch models were used to examine the psychometric properties of the FLQ-SF. More specifically, the factorial structure of the FLQ-SF was assessed using confirmatory factor analysis (CFA), the item fit was examined using the Rasch model, and the concurrent validity was evaluated using the correlation between the FLQ-SF, TPB elements, and FFQ. Results: CFA results confirmed the Persian FLQ-SF has a five-factor structure. Rasch models indicated that all the FLQ-SF items fit in the construct of food attitudes. Significant correlations between FLQ-SF and other instruments (TPB elements and FFQ) supported the concurrent validity of the FLQ-SF. Conclusions: The psychometric findings of the present study demonstrated that Persian FLQ-SF is a reliable and valid instrument. Therefore, the Persian FLQ-SF can be applied to assess food attitudes among Iranian women with breast cancer who are overweight.